The social worker speaks [ a history of social workers through the twentieth century - Burnham, David Michael (Ashgate, 2012)
"Since the war, histories of social work have concentrated on practice theory and methods, developments instigated by legislation, university training and professional status, but there has been little attention paid to who social workers were, what they believed, what they actually did, and what they thought of what they did. If part of the aim of this book is to remedy this partial coverage, another aim is to offer a more human history of social workers. There is too little celebration or humour in what has been published about the history of social workers; The Social Worker Speaks deliberately includes stories of how social workers behaved, their frustrations and triumphs, passions and occasional sins. So this is deliberately not a history of social work, but a history of social workers - the first of its kind"--Provided by publisher